Pengaruh Payment Gateway terhadap Kinerja Keuangan UMKM - Deka Anggun Lestari; Endah Dewi Purnamasari; Budi Setiawan (Jurnal Bisnis, Manajemen, dan Ekonomi, 2020)
Financial Technology (Fintech) is a combination of technology and financial services. There are several types of fintech, including Peer to Peer Lending, Risk and Investment Management, Market Aggregator, Payment, Clearing and Settlement, which changes an old innovation with digital technology. One widely used fintech is Payment Gateways such as OVO and Go-Pay, which encourage cashless society. One indicator that is implemented to measure Payment Gateway's financial performance is sales revenue. This study aims to examine the effect of Payment Gateway on the Financial Performance of Small Medium Enterprises (SMEs) in Palembang Indah Mall. Data were collected through questionnaires involving 53 respondents by using normality test, validity test, reliability test, coefficient of determination, and t-test. The result of the t-test and the coefficient of the determination indicates that the Payment Gateway variable significantly influences the financial performance of SMEs measured by sales revenue.